Political change and material culture in Middle to Late Bronze Age Canaan - Bechar, Shlomit (History, Archaeology, and Culture of the Levant, 2022)
Do shifts in material culture instigate administrative change, or is it the shifting political winds that affect material culture? This is the central question that Shlomit Bechar addresses in this book, taking the transition from the Middle to Late Bronze Age (seventeenth–fourteenth centuries BCE) in northern Canaan as a test case.Combining archaeological and historical analysis, Bechar identifies the most significant changes evident in architectural and ceramic remains from this period and then explores how and why contemporary political shifts may have influenced, or been influenced by, these developments. Bechar persuasively argues that the Egyptian conquest of the southern Levant—enabled by local economic decline following the expulsion of the Hyksos and the fall of northern Syrian cities—was the impetus for these changes in ceramics and architecture. Using a macro-typological approach to examine the ceramic assemblages, she also discusses the impact of the influx of Aegean imports, suggesting that while “attached specialists” were primarily responsible for ceramic production in the Middle Bronze Age, Late Bronze Age ceramics were increasingly made by “independent specialists,” another important result of the new administrative system created following Thutmose III’s campaign.An important contribution to our understanding of the transition between the Middle and Late Bronze Ages, this original and insightful book will appeal to specialists in the Bronze Age Levant, especially those interested in using ceramic assemblages to examine social and political change